2019
DOI: 10.14814/phy2.14246
|View full text |Cite
|
Sign up to set email alerts
|

Testing of novel spectral device sensor in swine model of airway obstruction

Abstract: Loss of a patent airway is a significant cause of prehospital death. Endotracheal intubation is the gold standard of care but has a high rate of failure and complications, making development of new devices vital. We previously showed that tracheal tissue has a unique spectral profile which could be utilized to confirm correct airway device placement. Therefore, the goals of this study were twofold: 1‐ to develop an airway obstruction model and 2‐ use that model to assess how airway compromise affects tissue re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Previously, our team showed that spectral reflectance could differentiate between esophageal and tracheal tissues in ex vivo swine, in vivo swine even during hypoxia, and human cadavers [12,13,20]. In all instances, there was a statistically significant difference in ratios B and Y between the tissue types, which we hypothesized could be used as a means to validate tracheal tube placement if the technology was built directly into the tube.…”
Section: Discussionmentioning
confidence: 89%
“…Previously, our team showed that spectral reflectance could differentiate between esophageal and tracheal tissues in ex vivo swine, in vivo swine even during hypoxia, and human cadavers [12,13,20]. In all instances, there was a statistically significant difference in ratios B and Y between the tissue types, which we hypothesized could be used as a means to validate tracheal tube placement if the technology was built directly into the tube.…”
Section: Discussionmentioning
confidence: 89%